2015
DOI: 10.1097/mnh.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced acute kidney injury

Abstract: Hydration still represents the most reliable strategy to prevent CI-AKI. New prophylactic strategies for acute kidney injury are still under investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 86 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…This means that tolvaptan increases renal blood flow without reducing the serum sodium level and could prevent renal medullary ischemia/hypoxia as a result of increased renal blood flow without aggravating heart failure if used for the prophylaxis of CI-AKI. Despite reports that diuretics can prevent CI-AKI, the effect of these drugs remains controversial [22]. Majumdar et al [23] found that forced euvolemic diuresis with saline, mannitol, and furosemide was associated with a significantly higher incidence of CI-AKI than saline hydration (50 vs. 28%, p = 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…This means that tolvaptan increases renal blood flow without reducing the serum sodium level and could prevent renal medullary ischemia/hypoxia as a result of increased renal blood flow without aggravating heart failure if used for the prophylaxis of CI-AKI. Despite reports that diuretics can prevent CI-AKI, the effect of these drugs remains controversial [22]. Majumdar et al [23] found that forced euvolemic diuresis with saline, mannitol, and furosemide was associated with a significantly higher incidence of CI-AKI than saline hydration (50 vs. 28%, p = 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…TMZ is a piperazine derivative, which is a inhibitor of mitochondrial long-chain 3-acyl coenzyme A. Basic research [29,30] confirmed that TMZ can inhibit the production of oxygen-free radical, reduce apoptosis, prevent mitochondrial swelling, enhance mitochondrial activity, and prevent cell lysis, thereby protecting the cell function. In addition, TMZ can improve the concentration of intracellular SOD, which is a part of the main substances in removing oxygen-free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery is a significant advance in efforts to find a way to mitigate the serious medical problem of CI‐AKI in interventional neurology and cardiology, and all other uses of iodinated contrast agents. Although there have been attempts to alter the molecular structure of iodinated contrast, none of these changes in the structure of low ionic or isoionic iodinated contrast agents have made a significant impact on the incidence of CI‐AKI …”
Section: Discussionmentioning
confidence: 99%